2019
DOI: 10.1029/2018ja026121
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Intra–D Ring Azimuthal Magnetic Field Profiles Observed on Cassini's Proximal Periapsis Passes

Abstract: We overview the properties of the azimuthal magnetic fields observed during the periapsis passes of the final 23 orbits of the Cassini spacecraft, including the partial orbit at end of mission, on near equatorial field lines passing inside of Saturn's D ring. The signatures are variable in form and amplitude, though generally approximately symmetric about the point where the spacecraft trajectory lies tangent to a flux shell, corresponding to where the ionospheric field line feet map closest to the equator, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(76 citation statements)
references
References 23 publications
(60 reference statements)
7
69
0
Order By: Relevance
“…It can be seen that the current begins to increase to positive values on D ring field lines both north and south and continues to increase near linearly with colatitude in the region inside the D ring, reaching peak values of ~1.5 MA/rad at the largest colatitudes reached, corresponding to ~71° in the northern hemisphere and ~98° in the southern hemisphere. This value is similar to those presented by Dougherty et al (), Khurana et al (), and Provan et al (). It seems clear from this profile, however, that the current is still rising strongly with colatitude in the innermost part of the region sampled, with the actual peak northward current flowing across the equatorial region remaining undetermined.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It can be seen that the current begins to increase to positive values on D ring field lines both north and south and continues to increase near linearly with colatitude in the region inside the D ring, reaching peak values of ~1.5 MA/rad at the largest colatitudes reached, corresponding to ~71° in the northern hemisphere and ~98° in the southern hemisphere. This value is similar to those presented by Dougherty et al (), Khurana et al (), and Provan et al (). It seems clear from this profile, however, that the current is still rising strongly with colatitude in the innermost part of the region sampled, with the actual peak northward current flowing across the equatorial region remaining undetermined.…”
Section: Resultssupporting
confidence: 93%
“…We now present current and current density results as described above for four representative intra-D ring passes. Provan et al (2019) have recently suggested a broad division of passes into four categories, though noting that the data generally display more a continuum of behaviors rather than completely distinct types. In essentially all cases, the field profiles show approximate symmetry about the magnetic equator, though differing in the number, form, and sign of the peaks in field observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we do not observe field perturbations of this magnitude, we conclude the upper limit of the current density to be 1 nA/m 2 . In addition, the azimuthal magnetic field could be influenced by other sources as shown by the fits performed by Provan et al (). Indeed, Hunt et al () showed the presence of the planetary period oscillations in the azimuthal field component during the closest approach of the ring‐grazing orbits prior to the Grand Finale.…”
Section: Location and Properties Of The Auroral Hissmentioning
confidence: 96%